LOCAL WISDOM OF SUNDANESE IN EDUCATION - Iwan Hermawan (Widyariset, 2012)
This study aimed to understand the phenomena that occur in the society, especially in the younger generation.The research method used was qualitative research methods. The locations of this inquiry are the areas wherethe Sundanese culture and language are practiced and maintained, and specifically the areas of the private highschools managed by the Pasundan Educational Foundation and Sundanese Educational Foundation (YayasanAtikan Sunda). The finding of this research shows that firstly, there are shifts in the view and attitude among theyoung Sundanese generation toward their own cultural value; secondly, the social studies teachers who teachSundanese culture are facing difficulties with the scarcity of resources and facilities; thirdly, the private highschools maintained by Pasundan Educational Foundation and Sundanese Educational Foundation are aware tothe needs and therefore committed to the task of the transmission of their culture and values.